The Effect of Specific Strength Training Using Artificial Sand Surfaces on Developing Some Physical And Biomechanical Indicators For Youth 200m Runners. (Journal of the College of Basic Education, 2025)
The rapid development in achieving international sports standards in various fields has helped specialists in the sports field to work diligently to search for new developments in sports training. This is in order to improve and develop the individual’s athletic abilities and bring him to the highest levels. This is evident through making maximum use of all the material capabilities surrounding the player, represented in the surrounding environment, and exploiting them in the field of training. The track and field game is one of the games that require strength, speed, endurance, motor and physical abilities, in addition to the use of sandy surfaces. To create differences in the physical and mechanical variables of 200m players, the research problem lies in developing modern training methods that break the monotony and boredom of the training units, in addition to raising the training level for the 200m event. The research aims to prepare a training curriculum using sand surfaces and finding differences for the training period on sand surfaces. The researcher assumed the existence of statistically significant differences between the pre- and post-tests of the research sample. The researcher chose young 200m players to conduct the experiment on. She concluded that receiving special strength training had a positive impact on the physical and mechanical variables of 200m runners.